Flux Transfer Events at a Reconnection‐Suppressed Magnetopause: Cassini Observations at Saturn. Issue 2 (17th February 2021) - Jasinski, Jamie M.; Akhavan‐Tafti, Mojtaba; Sun, Weijie; Slavin, James A.; Coates, Andrew J.; Fuselier, Stephen A.; Sergis, Nick; Murphy, Neil
Abstract: We present the discovery of seven new flux transfer events (FTEs) at Saturn's dayside magnetopause by the Cassini spacecraft and analyze the observations of all eight known FTEs. We investigate how FTEs may differ at Saturn where the magnetopause conditions are likely to diamagnetically suppress magnetic reconnection from occurring. The measured ion‐scale FTEs have diameters close to or above the ion inertial length d i ∼1–27 (median and mean values of 5 and 8), considerably lower than typical FTEs found at Earth. The FTEs magnetic flux contents are 4–461 kWb (median and mean values of 16 and 77 kWb), considerably smaller (<0.1%) than average flux opened during magnetopause compression events at Saturn. This is in contrast to Earth and Mercury where FTEs contribute significantly to magnetospheric flux transfer. FTEs therefore represent a negligible proportion of the amount of open magnetic flux transferred at Saturn. Due to the likely suppression of the two main growth‐mechanisms for FTEs (continuous multiple x‐line reconnection and FTE coalescence), we conclude that adiabatic expansion is the likely (if any) candidate to grow the size of FTEs at Saturn. Electron energization is observed inside the FTEs, due to either Fermi acceleration or parallel electric fields. Due to diamagnetic suppression of reconnection at Saturn's magnetopause, we suggest that the typical size of FTEs at Saturn is most likely very small, and that there may be more d i ∼1 FTEs present in the Cassini magnetometer data that have not been identified due to their brief and unremarkable magnetic signatures. Key Points: Eight Saturn ion‐scale flux transfer events (FTEs) are analyzed with diameters of d i ∼1–27 FTEs at Saturn are found to transfer negligible amounts of flux at Saturn's magnetosphere Evidence for electron energization is observed inside some of the FTEs, due to either Fermi acceleration or parallel electric fields